(3LjhehQahdhLjI GdHdGjG HefNaV GdOGNdI (B: s (3OQGSI ai GdLZQGajG GdWHjYI GdJWHjbjI HGSJNOGe fXe GdeYdheGJ GdLZQGajI h GdGSJTYGQ Yf HYO (B/ s - (3ei aJM Gddg EHQGgje aJM Gddg LHQjds; (3LhOI aJMi GdJQceGfi (B: s; (3eMeO YHOGdQMef MeOGf (B: s ((3GdbGgQI (B: s (3ei aJM Gddg EHQGgje aJM Gddg LHQjd (B: s, 2020)
(3jhLO efNaV GdOGNdI HbdH GdUMQGA GdZQHjI(B: (3h jJejR HhLhO XGgQI GdHdGjG GdeJNPI GeJOGOG jJeGKd eY GdGeJOGO GdYGe ddefNaV(B: (3h Je JUfja QhGSH GdHdGjG HefNaV GdOGNdI Gdi HdGjG Je JQSjHgG ai hSW GdHdGjSJhSjf h QhGSH HdGjG Je JQSjHgG ai ChGFd h hSW GdghdhSjf h QhGSH HdGjG GdfGJLI Yf YedjI GdQi(B: (3ceG JfGhdJ GdOQGSI NUGFU HjFI GdJQSjH ef MjK aJ G QJ GdQWhHI hGdLaGa hYhGed fTCJgG ShGA cGfJ HaYd GdChOjI Ch HaYd GdejGg GdLhajI h NUGFUgG GdQShHjI ef MjK WQjbI JQSjH WHbGJgG h GdYedjGJ GdLjhehQahdhLjI GdJi JYQVJ dgG hGdHYO GdCKQi h GdMVGQi dgG ef MVGQGJ aJQI GdHdGjSJhSjf h GdghdhSjf eQhQkG HGdMVGQGJ GdaQYhfjI h GdQheGfjI h QUO edGeM GdJONd GdHTQi GdMOjK YdjgG h WQb GSJZdGdgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GdLZQGajGs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdOGNdIs; (3HdGjGs; (3HdGjSJhSjfs